2015
DOI: 10.1111/all.12694
|View full text |Cite
|
Sign up to set email alerts
|

Variation in allergen content in sublingual allergen immunotherapy with house dust mites

Abstract: BackgroundAllergen immunotherapy is a treatment modality which can be applied using different vaccines. The aim of this study was to quantify and compare the allergen content of different house dust mites (HDM)’ sublingual treatments and to review the evidence on their efficacy.MethodsFive sublingual allergen immunotherapy (SLIT) products were ordered and purchased at an ordinary pharmacy and masked for blinding before the study was started. Detection of Dermatophagoides pteronyssinus and Dermatophagoides fari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Culture systems and manufacturing methods for each mite species are not harmonized within the industry. This scenario, coupled with the inherent variability associated with biological materials, explains the heterogeneity of products available on the market, which can differ greatly in terms of allergen composition and allergenicity (Brunetto et al ., ; Casset et al ., ; Moreno Benítez et al ., ). Standardization is a main concern for regulatory agencies, as exemplified by the new monographs of the European Pharmacopoeia (01/2017:1063 and 01/2017:2625).…”
Section: Introductionmentioning
confidence: 97%
“…Culture systems and manufacturing methods for each mite species are not harmonized within the industry. This scenario, coupled with the inherent variability associated with biological materials, explains the heterogeneity of products available on the market, which can differ greatly in terms of allergen composition and allergenicity (Brunetto et al ., ; Casset et al ., ; Moreno Benítez et al ., ). Standardization is a main concern for regulatory agencies, as exemplified by the new monographs of the European Pharmacopoeia (01/2017:1063 and 01/2017:2625).…”
Section: Introductionmentioning
confidence: 97%
“…Different investigators have consistently found major differences in the in vitro potency of liquid sublingual allergen immunotherapy (SL‐AIT) extracts available on the European market: manufacturer A dosing between 12 and 45 times was more diluted than manufacturer B over the whole range of allergens tested . To overcome the variability of SL‐AIT liquid dosing and to avoid the need for refrigeration, SLIT tablets were developed: the fast‐dissolving timothy grass pollen (TIM) tablet, Grazax/Grastek ® , and the 5‐grass pollen tablet, Oralair ® .…”
mentioning
confidence: 99%
“…Our method proved to be compatible with glycerol and phenol, the most common excipients in the formulation of skin prick test and sublingual immunotherapy (SLIT) products . In addition, the sensitivity of our method allows the analysis of highly diluted extracts (0.75 μg Der p 1/ml and 0.63 μg Der p 2/ml), equivalent to the lowest concentrated products cited in the literature . Further investigation is needed to confirm compatibility with other AIT products (e.g.…”
Section: Discussionmentioning
confidence: 99%